Developing a new business model for enabling research – the case of the ACPFG in Australia. (15th November 2006) - Agius, Stephanie C.; Corkindale, David; Dottore, Antonio G.; Gilbert, Michael
The way in which companies, research centres and educational institutions are organised and structured may provide a competitive advantage for commercialisation, in particular if companies are dependent on the deployment of complementary assets and capabilities by third parties. This paper presents the case of the Australian Centre for Plant Functional Genomics (ACPFG), a private agricultural biotechnology (agbiotech) company specialising in early stage Research and Development (R&D) to produce superior adapted cereal varieties, tolerant to abiotic stress conditions such as drought, frost, salt, or mineral toxicity, all of which have a direct and negative impact on plant growth and crop productivity. The organisational structure of the company has been influenced and shaped by Government policy, shareholders expectations and trends in the agbiotech industrial organisation. It has proved attractive to potential alliance partners for collaborative R&D and commercialisation. We present the ACPFG as a new business model to fund basic research and facilitate technology transfer.